MicroRNA-mediated autophagy and drug resistance in cancer: mechanisms and therapeutic strategies - Jinxing Wei; Xianghui Wang; Duo Yu; Yanyang Tu; Yaoyu Yu (Discover Oncology)
Abstract This paper provides an exhaustive overview of the intricate interplay between microRNAs (miRNAs) and autophagy in the context of human cancers, underscoring the pivotal role these non-coding RNAs play in modulating autophagic pathways and their implications for cancer development, progression, and resistance to therapy. MiRNAs, as critical regulators of gene expression post-transcription, influence various biological processes, including autophagy, a catabolic mechanism essential for cellular homeostasis, stress response, and survival. The review meticulously delineates the mechanisms through which miRNAs impact autophagy by targeting specific genes and signaling pathways, thereby affecting cancer cell proliferation, metastasis, and response to chemotherapy. It highlights several miRNAs with dual roles, acting either as oncogenes or tumor suppressors based on the cellular context and the specific autophagic pathways they regulate. The paper further explores the therapeutic potential of targeting miRNA-autophagy axis, offering insights into novel strategies for cancer treatment through modulation of this axis. Emphasizing the complexity of the miRNA-autophagy relationship, the review calls for more in-depth studies to unravel the nuanced regulatory networks between miRNAs and autophagy in cancer, which could pave the way for the development of innovative therapeutic interventions and diagnostic tools.